Modelling of IEEE 802.11 wireless LAN and medium access control layer performance analysis - Lu, Wei Wen. (2008)
The focus of this dissertation is on modelling, simulation and performance evaluation of the wireless LAN MAC layer. Optimized Network Simulation Tool (OPNET), one of the most widely used general-purpose network simulators, is used to develop the wireless LAN simulation model.